2015
DOI: 10.1002/aur.1579
|View full text |Cite
|
Sign up to set email alerts
|

The developmental trajectory of contrast sensitivity in autism spectrum disorder

Abstract: Autism Spectrum Disorder (ASD) is characterized by a detail-driven visual processing strategy, evidence for which has been based largely on cross-sectional studies in small participant groups of limited age ranges. It is therefore unknown when sensitivity to detailed information emerges and develops in ASD. Contrast sensitivity to sinusoidal gratings of different spatial frequencies (0.5, 1, 2, 4, and 8 cycles per degree (cpd)) was measured for 34 participants with ASD and 55 typically developing participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 58 publications
1
9
0
1
Order By: Relevance
“…4,41 They are also congruent with results in mildly impaired patients (stages 1-2) in a study assessing contrast sensitivity across all stages of symptom severity. 5 Moreover, the finding of reduced contrast sensitivity in the midfrequency range in PD bears similarity to findings obtained in patients with autism spectrum disorder (ASD): Reduced midfrequency range static contrast sensitivity has been reported in children and adolescents 42,43 as well as adults. 44 Many parts of the visual system have been implicated as the cause for visual deficits, such as the retina, where thinning of the inner retinal nerve fiber layer and decreased dopamine concentration seem to mirror the loss of dopaminergic neurons in the basal ganglia.…”
Section: Discussionsupporting
confidence: 69%
“…4,41 They are also congruent with results in mildly impaired patients (stages 1-2) in a study assessing contrast sensitivity across all stages of symptom severity. 5 Moreover, the finding of reduced contrast sensitivity in the midfrequency range in PD bears similarity to findings obtained in patients with autism spectrum disorder (ASD): Reduced midfrequency range static contrast sensitivity has been reported in children and adolescents 42,43 as well as adults. 44 Many parts of the visual system have been implicated as the cause for visual deficits, such as the retina, where thinning of the inner retinal nerve fiber layer and decreased dopamine concentration seem to mirror the loss of dopaminergic neurons in the basal ganglia.…”
Section: Discussionsupporting
confidence: 69%
“…Guy et al examined contrast sensitivity (using sinusoidal gratings from 0.5 to 8 cpd) in children with ASD (n = 34) between the ages of 6–16 years, and correlated performance with the age of the child. They reported a relative lack of sensitivity to mid‐spatial frequencies (8 cpd) in ASD compared with age‐matched controls, and also suggested that children with ASD have a different developmental trajectory for maturation and refinement of contrast sensitivity performance.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
“…The perception of individuals with autism has been shown to be more veridical, closer to the actual sensory input, and less influenced by cognitive biases, including attention, demand characteristics, and prior experiences than those of TD individuals [Baron-Cohen, Ashwin, Ashwin, Tavassoli, & Chakrabarti, 2009;Bonnel et al, 2010;Gonzalez-Gadea et al, 2015;Guy, Mottron, Berthiaume, & Bertone, 2016;Mottron et al, 2006;Mottron, Dawson, & Soulieres, 2009]. In addition, perceptual processing in ASD has been shown to be enhanced, with better detection [O'Riordan, 2004;O'Riordan et al, 2001;Plaisted et al, 1998] and discrimination abilities [Baron-Cohen et al, 2009;Guy et al, 2016;Jemel, Mimeault, Saint-Amour, Hosein, & Mottron, 2010;O'Riordan et al, 2001;Plaisted et al, 1998] noted across sensory modalities [Bonnel et al, 2003[Bonnel et al, , 2010Gomot et al, 2006Gomot et al, , 2011Gomot, Belmonte, Bullmore, Bernard, & Baron-Cohen, 2008;Guy et al, 2016;Mottron et al, 2006], and across development from infancy to adulthood [Gliga et al, 2015;Kaldy et al, 2011;O'Riordan, 2004;O'Riordan et al, 2001] for low level perceptual features. Manifestations of enhanced perceptual functioning seem to be more apparent in individuals with ASD who have a history of speech onset delay [Barbeau, Soulières, Dawson, Zeffiro, & Mottron, 2013;Eigsti & Fein, 2013;Heaton, Hudry, Ludlow, & Hill, 2008;Jarvinen-Pasley & Heaton, 2007;Jones et al, 2009], and thus inconsistent findings in the literature may be due to the inclusion of individuals with and without...…”
Section: Enhanced Perceptual Functioning In Asdmentioning
confidence: 99%